Diseño e implementación de una máquina semiautomática de pesado y sellado de productos granulados en el Supermercado Castro. - Tepán Tenempaguay, Alex Wladimir (2020)
At present, Canton Tisaleo Province of Tungurahua is one of the main distributors of granular products in the parishes, so it is necessary to have efficient weighting and sealing. The project arises from the need for a machine that allows to reduce the weighting and sealing time and becoming easy to operate. The main objective is the design and implementation of a semiautomatic weighting and sealing machine for granulated products in the Castro supermarket. The operation of the semiautomatic machine was established as an electronic system for weighting and mechanical system for sealing, which uses an Admega 328 microcontroller that allows us to control the input variables (selectors, pushbuttons, weight sensor) and output (reducing motor, pilot light, servo motor, LCD). The weighting is done by the rotation control of an endless screw. The product flows to the weighing hopper, and after obtaining the programmed quantity is discharged to the sheath for sealing. The weighting and sealing process can be displayed on an LCD. The results obtained from the implementation determined that the machine reduced the time and obtained the exact weight in contrast to the manual process.